Who benefits from the intervention? Correlates of successful BMI reduction in the Texas Childhood Obesity Demonstration Project (TX‐CORD). - Barlow, Sarah E.; Durand, Casey; Salahuddin, Meliha; Pont, Stephen J.; Butte, Nancy F.; Hoelscher, Deanna M. (Pediatric Obesity, 2020)
Background: Many childhood obesity intervention studies report mean outcomes but do not explore the variation in responses and the characteristics of those who respond well. Objective: To identify child and family characteristics associated with improvement in the primary outcome, %BMIp95, of the Texas Childhood Obesity Research Demonstration project (TX‐CORD). Methods: The 12‐month TX‐CORD secondary prevention study randomized 549 children, ages 2 to 12 years, with BMI ≥85th percentile to the intensive intervention vs. the comparison program, with measurements at baseline, 3‐, and 12‐months. A growth mixture model was used to identify mutually exclusive latent %BMIp95 trajectories. Latent class regression tested associations between baseline characteristics and latent class membership. Results: A 2‐class solution emerged after accounting for the effect of intervention randomization. Latent Class 1 participants (86% of sample) were characterized by mild‐to‐moderate obesity and demonstrated a significantly greater response to the intensive intervention between 0 and 3 months (slope‐on‐group = −0.931, p = 0.03). A rebound between 3 and 12 months was not significantly different between arms. Latent Class 2 participants (14%), who had severe obesity, demonstrated no difference in response between intervention groups. Characteristics associated with Class 1 membership included younger age (2–5 years vs. 6–12 years: OR 3.70, p =.035) and lower maternal BMI category (< 35 kg/m2 vs. ≥ 35 kg/m2: OR 7.14, p <.0001). Conclusions: The optimal target population for the intensive intervention are children who have milder obesity, are younger, and do not have a mother with severe obesity. Children with severe obesity may require different approaches.